Development and identification of Verticillium wilt-resistant upland cotton accessions by pyramiding QTL related to resistance - Xiu-hua GUO; Cai-ping CAI; Dong-dong YUAN; Ren-shan ZHANG; Jing-long XI; Wang-zhen GUO (Journal of Integrative Agriculture, 2016)
Cotton Verticillium wilt is a serious soil-borne disease that leads to significant losses in fiber yield and quality worldwide. Currently, the most effective way to increase Verticillium wilt resistance is to develop new resistant cotton varieties. Lines 5026 and 60182 are two Verticillium wilt-resistant upland cotton accessions. We previously identified a total of 25 quantitative trait loci (QTLs) related to Verticillium wilt resistance from 5026 and 60182 by assembling segregating populations from hybridization with susceptible parents. In the current study, using 13 microsatellite markers flanking QTLs related to Verticillium wilt resistance, we developed 155 cotton inbred lines by pyramiding different QTLs related to Verticillium wilt resistance from a filial generation produced by crossing 5026 and 60182. By examining each allele's effect and performing multiple comparison analysis, we detected four elite QTLs/alleles (q-5/NAU905-2, q-6/NAU2754-2, q-8/NAU3053-1 and q-13/NAU6598-1) significant for Verticillium wilt resistance, pyramiding these elite alleles increased the disease resistance of inbred lines. Furthermore, we selected 34 elite inbred lines, including five lines simultaneously performing elite fiber quality, high yield and resistance to V. dahliae, 14 lines with elite fiber quality and disease resistance, three lines with high yield and disease resistance, and 12 lines with resistance to V. dahliae. No correlation between Verticillium wilt resistance and fiber quality traits/yield and its components was detected in the 155 developed inbred lines. Our results provide candidate markers for disease resistance for use in marker-assisted breeding (MAS), as well as elite germplasms for improving important agronomic traits via modern cotton breeding.